Analysis Of The Effect Of Carbide Cutting Angle On The Surface Roughness Of Aisi 4337 Steel In Turning Axle Rail Shafts Without Cutting Fluid - Suhardi Napid; Ahmad Bakhori (CV. AFDIFAL MAJU BERKAH, 2025)
Varying cutting angles are applied to understand the relationship between cutting angles and machining result characteristics, such as surface roughness (Ra). Surface roughness as a dependent variable is influenced by machining parameters, namely depth of feed. Cutting angle, cutting speed and feed speed as independent variables. The aim of the research activity is to analyze the effect of variations in the cutting angle of carbide tools and identify the optimum cutting angle on the surface quality of the axle rail shaft from AISI 4337 steel processed using the dry turning method. The research was carried out experimentally, which had 9 specimens as test material to obtain surface roughness values ​​with variations in cutting angles using a CNC lathe without cutting fluid and a surface test tool. Test data is provided with machine spindle rotation speeds, namely 1200 rpm, 1400 rpm and 1600 rpm. Variations in cutting angles of 25o, 55o, 85o and feeds of 0.1 mm/r, 0.15 mm/r, 0.2 mm/r and a constant cutting depth of 1 mm are used for the dry turning process which is commonly used in industry to reduce the environmental impact . The average surface roughness (Ra-avg) values ​​of 3.05 μm, 2.35 μm, 1.64 μm obtained as a function of cutting angle are part of the optimum cutting conditions on HP9. From the analysis, it was found that the most optimum cutting angle (Kr) was an angle of 85o with an average surface roughness value (Ra-avg) of 1.64 μm as shown in figure 4.3. The results show that larger cutting angles tend to produce surfaces with lower roughness, while smaller angles can increase the tool wear rate. Factors such as cutting speed, depth of cut, and feed rate also influence the results significantly. This research provides important insights for the optimization of machining processes in industrial applications.